Botulinum neurotoxin A and an engineered derivate targeted secretion inhibitor (TSI) A enter cells via different vesicular compartments. (2nd January 2016) - Fonfria, Elena; Donald, Sarah; Cadd, Verity A.
Abstract: Botulinum neurotoxins (BoNTs) are highly potent multi-domain proteins, responsible for botulism in animals and humans. The modular structural organization of BoNTs has led to the development of novel engineered bio-therapeutic proteins called targeted secretion inhibitors (TSIs). We report here that botulinum neurotoxin A (BoNT/A) and a TSI/A in which the neuronal binding domain of BoNT/A has been substituted by an epidermal growth factor (EGF) ligand, named EGFR-targeted TSI/A, exploit different routes to gain entry in the same in vitro neuroblastoma cell system, SiMa cells. We found that the EGF ligand conferred the affinity to the EGFR-targeted TSI/A at the EGF receptor when compared to an untargeted TSI/A and also the ability to internalize into the cells and cleave its cytosolic target protein SNAP-25. Using high content analysis we found that both BoNT/A and the EGFR-targeted TSI/A enter the cell in a concentration-dependent manner and in compartments which are able to translocate the proteins into the cytosol within 4 h. The EGFR-targeted TSI/A internalized into a compartment which gave a punctate staining pattern by immunofluorescence and partially overlapped with structures positive for the early endosomal marker EAA1; whereas BoNT/A did not internalize into a punctate compartment but did so in an acidifying compartment consistent with local synaptic vesicle recycling. These findings show that the BoNT/A translocation domain, common to both BoNT/A and the EGFR-targeted TSI/A, is a versatile tool for cytosolic delivery from distinct intracellular vesicular compartments.